[Retracted] Inventory of wild animals along the Bengkunat-Sanggi Road in Bukit Barisan Selatan National Park, Lampung Province, Indonesia - GUNARDI DJOKO WINARNO; YOB CHARLES; CHARLES ANTONIO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Winarno GD, Charles Y, Antonio C. 2024. Inventory of wild animals along the Bengkunat-Sanggi Road in Bukit Barisan Selatan National Park, Lampung Province, Indonesia. Biodiversitas 25: 2917-2924. The quality of the West Sumatra route Bengkunat-Sanggi in Indonesia has significantly improved since 2005, what was originally a dirt road became an asphalt road, leading to an increase in its utilization by various types of vehicles such as motorbikes, sedans, jeeps, buses, and trucks. This condition has an impact on wildlife activities along the road. The sound of vehicles and lights turning on at night can attract animals to move towards the road, which can endanger these animals. On the other hand, lots of vehicles crossing the road can cause animals to run far away because they are disturbed, so it is thought that the animal's movement area will also change. This study aims to explore the effects of road construction on wildlife presence, with a specific emphasis on endangered species like tigers, elephants, and rhinoceroses near the Bukit Barisan Selatan National Park (BBSNP), Indonesia. Camera traps are currently being employed to record animals living in the vicinity of roads, including those that have fallen victim to vehicle collisions. The division of wildlife habitats by roads poses a substantial threat to their survival and functionality. The presence of traffic roads has been linked to an increase in accidents involving animals attempting to cross the road. Some animals appear to be disturbed by the noise generated by vehicles, leading to a reduction in their home range. Initial monitoring results at the onset of road construction indicated a higher presence of threats wild animals, specifically tiger (Panthera tigris subsp. sumatrae Pocock, 1929), Sumatran elephant (Elephas maximus subsp. sumatranus Temminck, 1847) and Sumatran rhino (Dicerorhinus sumatrensis G.Fischer, 1814). To safeguard the wildlife along the Sanggi Bengkunat Road, a comprehensive approach involving all stakeholders and ensuring orderly behavior of drivers while navigating the road is imperative.